Analysis Of Handling Of Fertilizer Raw Material Stock Delay Using Safety Stock And Reorder Point Methods In Gresik Fertilizer Company - Nisa, Devy Ana Choirun; Aslamiyah, Suaibatul (Jurnal Economic Resource, 2024)
This research analyzes the handling of delays in stock of fertilizer raw materials at the Pupuk Gresik Company by applying the safety stock and reorder point methods. The main problem faced by the company is the lack of supply of raw materials due to short arrival times and seasonal demand, which has an impact on smooth production. This research uses a qualitative descriptive approach with observation methods, interviews with the President Director and Head of Operations, as well as analysis of historical data related to the use of raw materials, lead time and delivery delays. The research results show that companies still use manual recording in inventory management, which contributes to low accuracy in stock planning. By implementing the safety stock and reorder point methods, companies can determine the optimal amount of reserve inventory and more effective reorder points to achieve the desired service level (95%). The implementation of this method is expected to reduce the risk of delays in raw materials and increase operational efficiency at the Gresik fertilizer company.